ISTHMIC-CERVICAL INSUFFICIENCY: AS A CAUSE OF PERINATAL LOSS - Duschanova Zaynab Atabayevna (Scholar Express Journals, 2022)
The purpose of the study was to determine the prevalence of isthmic-cervical insufficiency (ICI) in women of the Khorezm region and to assess the clinical and anamnestic features of these patients. Material and methods. Simultaneous cross-sectional study. 343 pregnant women at 18–21 weeks of gestation were included in the study. All patients underwent transvaginal ultrasonography. Criteria for the diagnosis of CI were shortening of the detection of the cervix <25 mm and/or dilatation of the cervical canal >10 mm. Results. As a result of the study, it was found that the prevalence of CCI among women in the Khorezm region is 9.3 per 1000 women. At the same time, 48% of patients were asymptomatic, 14.8% had a history of surgical interventions on the cervix, 19.7% had miscarriages >14 weeks, and 10% had complicated births. Conclusion. The study showed a high prevalence of CI in the Khorezm region, the main risk factors should be considered surgical treatment of cervical diseases, premature birth and late miscarriages in anamnesis
Keywords: : Isthmic-Cervical Insufficiency; Preterm Birth; Anamnesis; Transvaginal Ultrasonography